Tabu Search Against Permutation Based Stream Ciphers - Iwona Polak; Marcin Boryczka (International Journal of Electronics and Telecommunications, 2018)
Encryption is one of the most effective methods of securing data confidentiality, whether stored on hard drives or transferred (e.g. by e-mail or phone call). In this paper a new state recovery attack with tabu search is introduced. Based on research and theoretical approximation it is shown that the internal state can be recovered after checking 252 internal states for RC4 and 2180 for VMPC.